Chief Minister Department, Human Resource Department (HRM) / Noorlida Wajdi - Wajdi, Noorlida (Universiti Teknologi MARA, Sarawak, 2013)
Sarawak Civil service was first known as Sarawak Administrative Service (SAS) established by James Brooke when he was given the territory of Sarawak in 1841. In 1842, James Brooke proclaimed Rajah of Sarawak. Introduced by Rajah James Brooke, Sarawak administration depicts from European style of administration originated from India and Africa. The formation of Sarawak Administrative service and the selection of officers were mainly from Brooke relatives and colleagues. Two departments that were established in 1864 are Post Office and Treasury department with a number of staff by only 4 Europeans and 2 Malays. Below is Rajah Brooke Crest, the symbol of Rajah Administration and the Latin words “Dum Spiro Spero” that mean “While I Breath I Hope”. Arthur Crookshank was among the early European officers. He was the 2nd Chief Secretary from 1846-1873.